The Jews, the Holocaust, and the public : the legacies of David Cesarani - Allwork, Larissa HerausgeberIn; Pistol, Rachel HerausgeberIn (The Holocaust and its contexts, 2019)
Part I:Introduction --1.Introduction: The Lives and Legacies of David Cesarani /Larissa Allwork and Rachel Pistol.2.David Cesarani: A Historian with Breadth, Depth, and the Flair of a Raconteur /Robert Rozett.Part II.Minorities and Nationalisms --3.Zionism and the British Labour Party /David Feldman.4.History, Politics and Nationalism in Ireland and Israel: Legacies of 1922 and 1948 /Shane Nagle.5.Remembering the Internment of 'Enemy Aliens' During the Second World War on the Isle of Man, and in Australia and Canada /Rachel Pistol.Part III:Perspectives on the Holocaust --6.The Decision to Exterminate the Jews of Europe /Richard J. Evans.7.The 1940 'Easter Pogrom' in Warsaw from the Perspective of the Jewish Witnesses /Katarzyna Person.8.The Ideologue as Genocidaire: Alfred Rosenberg and the Murder of the Jews in the Soviet Union /Jürgen Matthäus.9.British and American Voluntary Organizations in Liberated Bergen-Belsen Concentration Camp: An Unknown Story /Johannes-Dieter Steinart.Part IV:Nazi Crimes and Their Legacies --10.The United Kingdom War Crimes Investigation Teams after World War II /Robert Sherwood.11.Britain and the Eichmann Trial: An Unexamined Aspect in 'Bystander Studies' /Joseph Snee.12.In Advance of the Broken Image: Gerhard Richter and Gustav Metzger's Confrontations with Nazi Criminality /Larissa Allwork.Part V:Public History and Holocaust Commemoration --13.Constructing a British Holocaust Narrative: A British Reading of Co-presents to the Shoah /Aimee Bunting and Tony Kushner.14.David Cesarani and the Creation of the Imperial War Museum's Holocaust Exhibition /Suzanne Bardgett.15.David Cesarani and UK Holocaust Memorial Day /Rachel Century and Olivia Marks-Woldman.16.After the Holocaust: Facing the Nazi Past in British and International Perspective-An Interview with David Cesarani /Larissa Allwork.Part VI:Afterword --17.Afterword /David Cesarini, Byran Cheyette, and Dawn Waterman.